2021
DOI: 10.3389/fendo.2021.757566
|View full text |Cite
|
Sign up to set email alerts
|

Acute Illness and Death in Children With Adrenal Insufficiency

Abstract: BackgroundAdrenal Insufficiency (AI) can lead to life-threatening Adrenal Crisis (AC) and Adrenal Death (AD). Parents are trained to prevent, recognise and react to AC but there is little available information on what parents are actually doing at home to manage symptomatic AI.MethodsThree approaches were taken: (A) A retrospective analysis of patient characteristics in children and young people with AD over a 13-year period, (B) An interview-aided questionnaire to assess the circumstances around AC in childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Although this has not been previously reported in PKT recipients, Worth et al. reported that 30% of their cohort (children with AI, n = 127) had a recorded emergency department visit due to acute illness, 49 and Eyal et al. reported recurrent hospital admissions were significantly associated with adrenal crisis among children with AI 50 .…”
Section: Discussionmentioning
confidence: 66%
“…Although this has not been previously reported in PKT recipients, Worth et al. reported that 30% of their cohort (children with AI, n = 127) had a recorded emergency department visit due to acute illness, 49 and Eyal et al. reported recurrent hospital admissions were significantly associated with adrenal crisis among children with AI 50 .…”
Section: Discussionmentioning
confidence: 66%
“…According to a recent study by Worth et al, the rate of death due to an adrenal crisis among children with adrenal insufficiency has remained high. The correct GC stress dose for different acute illnesses has the potential to prevent death .…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms of AI may initially be nonspecific and include growth faltering, lethargy, poor feeding, abdominal pain, vomiting and weight loss. 3 Infants may develop hypoglycaemia irrespective of the cause of AI. A recent review provides a comprehensive summary of causes of AI in children and adults.…”
Section: Reviewmentioning
confidence: 99%
“…Suppression of ACTH leading to AI may also result from exogenous high dose glucocorticoid use. Symptoms of AI may initially be non-specific and include growth faltering, lethargy, poor feeding, abdominal pain, vomiting and weight loss 3. Infants may develop hypoglycaemia irrespective of the cause of AI.…”
Section: Introductionmentioning
confidence: 99%